2022
DOI: 10.3390/nu14204313
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Week Follow-Up Study on the Sustained Effects of Prolonged Water-Only Fasting and Refeeding on Markers of Cardiometabolic Risk

Abstract: (1) Background: Chronic inflammation and insulin resistance are associated with cardiometabolic diseases, such as cardiovascular disease, type 2 diabetes mellitus, and non-alcoholic fatty liver disease. Therapeutic water-only fasting and whole-plant-food refeeding was previously shown to improve markers of cardiometabolic risk and may be an effective preventative treatment but sustained outcomes are unknown. We conducted a single-arm, open-label, observational study with a six-week post-treatment follow-up vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…This large reduction was observed even though 5/17 participants with stage 2 HTN on enrollment continued to have stage 2 HTN six weeks after the intervention. The reductions in BP correlate with the timing of the intervention and are in agreement with other studies, [12; 13; 15; 36; 37] setting a precedent for future randomized controlled trials. Results from the 12mFU visit are inconclusive due to participant dropout, but the median SBP remained below 130 mmHg and of the 6/17 participants who resumed anti-hypertensive medications, only one had SBP below 120 mmHg.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This large reduction was observed even though 5/17 participants with stage 2 HTN on enrollment continued to have stage 2 HTN six weeks after the intervention. The reductions in BP correlate with the timing of the intervention and are in agreement with other studies, [12; 13; 15; 36; 37] setting a precedent for future randomized controlled trials. Results from the 12mFU visit are inconclusive due to participant dropout, but the median SBP remained below 130 mmHg and of the 6/17 participants who resumed anti-hypertensive medications, only one had SBP below 120 mmHg.…”
Section: Discussionsupporting
confidence: 89%
“…These data contribute to a growing body of evidence suggesting that medically supervised prolonged water-only fasting followed by whole-plant-food refeeding may be a safe and feasible treatment option for various health conditions, particularly obesity and hypertension. [12; 13; 15; 36; 37] Importantly, the fasting and refeeding intervention in this study was conducted in a residential setting using a protocol in which participants had access to medical support 24 hours per day and are individually examined twice daily to identify potentially serious complications. Even though the prolonged intervention takes place in a residential setting, participants reported that they found it to be highly acceptable and preferable to conventional treatment with anti-hypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may lessen mechanical load on the joints of the lower extremities, possibly contributing to pain reduction (59). Furthermore, lipid metabolism is improved by fasting (60). Even in patients with normal BMI, metabolic factors have shown to be associated with disease severity (61).…”
Section: Discussionmentioning
confidence: 99%